2017
DOI: 10.1111/vec.12601
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of coyote attacks in dogs: 154 cases (1997–2012)

Abstract: Coyote attacks on dogs are a problem in Southern California and are associated with substantial morbidity and mortality, especially in dogs with wounds to the thorax. Aggressive management involving surgical wound repair was associated with survival to discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…Size of the animal or person is a risk factor for being bitten by dogs, and also is associated with mortality from these injuries 8,14,19 . Our results support these findings because the majority of animals that were included were miniature equids or ponies compared to the general case population of all 3 centers.…”
Section: Discussionsupporting
confidence: 80%
“…Size of the animal or person is a risk factor for being bitten by dogs, and also is associated with mortality from these injuries 8,14,19 . Our results support these findings because the majority of animals that were included were miniature equids or ponies compared to the general case population of all 3 centers.…”
Section: Discussionsupporting
confidence: 80%
“…Sensitivity (%) Specificity (%) Surgical intervention was predictive of survival to discharge in canine patients that experienced either blunt or penetrating trauma with a surgical procedure performed, including wound debridement. 9,24 One study found a 7.1-fold increased chance of surviving to hospital discharge if surgical intervention was performed; another study involving coyote bites had a 15-fold increased chance of survival with surgical wound repair. 24 Haemodynamic compromise or death within hours of arrival to the hospital and owner desire to humanely euthanatize due to the severity of the wounds and financial constraints were quoted as the reasons that dogs did not undergo a surgical procedure in the study.…”
Section: Studymentioning
confidence: 99%
“…9,24 One study found a 7.1-fold increased chance of surviving to hospital discharge if surgical intervention was performed; another study involving coyote bites had a 15-fold increased chance of survival with surgical wound repair. 24 Haemodynamic compromise or death within hours of arrival to the hospital and owner desire to humanely euthanatize due to the severity of the wounds and financial constraints were quoted as the reasons that dogs did not undergo a surgical procedure in the study. 24 Also, intensive perioperative monitoring, intravenous analgesics and anti-microbial therapy were used in all patients that had surgery.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations